ANALISIS CAPITAL BUDGETING SEBAGAI ALAT PENGAMBILAN KEPUTUSAN INVESTASI: Studi Kasus - Ananda Setiawan; Andika Puspita Sari (Universitas Ahmad Dahlan Indonesia, 2018)
A good investment decision analysis has to go through to find out the work done will benefit or not. To avoid the losses that investors received, then investors should know the proposed investment with long-term risks will be accepted. The purpose of this research is to analyze the feasibility of investment of fixed assets in the form of replacement of fixed assets fixed assets the old with new in the MSMes Serabi in Surakarta, Central Java by using techniques of Capital Budgeting. This research method is the method of the description with quantitative approach. Data analysis using the latest financial reports to count ARR, PP, NPV, and PI. Data analysis of the results ARR 126.6 % > 20% the investment received, PP 5.13 month < 5 years then the investment received, NPV 41,682,000 > 0 then received investments, PI 11.69 > 1 then received investments. From research done then capital budgeting can be used as a decision-making tool investment fixed assets on the MSMes Serabi Surakarta to anticipate long-term losses.